Silently seizing : common, unrecognized and frequently missed seizures and their potentially damaging impact on individuals with autism spectrum disorders : an essential guide for parents and professionals - Haines, Caren (AAPC Pub., 2012)
A new way to look at some autistic behavior as the result of seizures rather than the autism itself. Includes up-to-date research and practical strategies.--